The Outer And Inner Corners Of The Base Of The Conflict - A.Taha, Qahtan (Opción, 2019)
Walk in this argument leads to acceptance that the pillars of the rule of conflict are not like other pillars of the other legal rules. But this conclusion does not seem to make sense. In fact, the rule of conflict shares with the other rules of law elements in which no legal rule can be established. However, they are sep- arated from them in subjectivity that demonstrates their specificity and helps them to fulfill the function entrusted to them by the codified, as noted above. This research will be divided into two sections as follows: The first topic: the external pillars of the base of conflict. The second topic: the internal pillars of the base of conflict. The first topic External Staff We will divide this topic into two requirements as follows: The first requirement: the external elements of the legal rule in general. The second requirement: the external elements at the base of the conflict.